Optimized Control for Dynamical Performance of the Polishing Robot in Unstructured Environment - Zhong Luo; Shuxian Yang; Yilan Sun; Hongyi Liu (Shock and Vibration)
In this paper, the dynamical performance of polishing robot working in unstructured environment is investigated. Structure mechanism and operating principle of a polishing robot are introduced firstly, and its dynamical model is established. Then, a S-shaped acceleration-deceleration path planning method and a human-simulated intelligent control (HSIC) strategy are proposed. The S-shaped acceleration-deceleration path planning method is to switch the magnitude and direction of the abrupt velocities between motion sections in order to improve the work efficiency, the smoothness of movement and the processing accuracy. The HSIC control strategy is built based on the unstructured environment information measured by ultrasonic sensors, in which the appropriate programs prepared in advance are determined according to the size and sign of both the control error and its change rate. Simulation results show that the intelligent control strategy combining with optimum path planning method are effective to reduce the structure vibration, to improve the stability and the control accuracy of the polishing robot system.